Resilience assessment and enhancement evaluation of power distribution systems subjected to ice storms. (February 2023) - Hou, Guangyang; Muraleetharan, Kanthasamy K.; Panchalogaranjan, Vinushika; Moses, Paul; Javid, Amir; Al-Dakheeli, Hussein; Bulut, Rifat; Campos, Richard; Harvey, P. Scott; Miller, Gerald; Boldes, Kirby; Narayanan, Maha
Highlights: A probabilistic framework for assessing and evaluating the enhancements of the ice storm resilience of power distribution systems is developed. Fragility models of power distribution components subjected to ice storms are developed. Three failure modes of power distribution components induced by trees, ice, and wind, are investigated for the first time. The impact of tree failures on the resilience of power distribution systems is thoroughly investigated. Abstract: Overhead power distribution systems are very susceptible to ice storms. Each year power outages due to ice storms result in extensive economical loss and restoration costs all around the world. Climate change and aging further highlight the need for resilient power distribution systems against ice storms. This paper proposes a probabilistic framework for assessing and evaluating the enhancements of the ice storm resilience of power distribution systems, with a focus on fragility modeling of power distribution components (i.e., power poles and wires). The framework is able to assess the impact of ice storms on the resilience of power distribution systems and evaluate the cost-effectiveness of resilience enhancement strategies such as upgrading poles and vegetation management. Specifically, the limitations of tree-induced risk assessment in previous studies are overcome by developing fragility models of tree-induced component failures and using an empirical tree damage fragility function. The fragility of distribution components subjected to ice storms is thoroughly investigated by considering four different failure modes and the effect of wind attack angle. The proposed framework is demonstrated with a power distribution network in Oklahoma.